Sistem Keamanan Jaringan Local Area Network Menggunakan Teknik De-Militarized Zone - Anugrah, Ino; Rahmanto, Raden Hengki (LPPM Universitas Islam 45 Bekasi, 2017)
ABSTRACT Islamic Universityâ€45â€ computer network needs a safe network to strengthen the network security systems to protect servers from attacks such as Port Scanning and DoS attack (Denial of Service). One of the network security techniques is De-Militarized Zone (DMZ) that is a mechanism to protect the internal system from hacker attacks or other parties who want to enter the system with no access. The purpose of this Project is to implement LAN network security system using De-Militarized Zone (DMZ) technique, with a single firewall that supports the internal and external networks. The results of the DMZ technique implementation at the Islamic University's